Sensitive determination of cadmium using solidified floating organic drop microextraction-slotted quartz tube-flame atomic absorption spectroscopy - Akkaya, Erhan; Chormey, Dotse Selali; Bakirdere, Sezgin (SPRINGER, 2017)
In this study, solidified floating organic drop microextraction (SFODME) by 1-undecanol was combined with slotted quartz tube flame atomic absorption spectrometry (SQT-FAAS) for the determination of cadmium at trace levels. Formation of a complex with 4,4 ' dimethyl- 2,2 '-bipyridine facilitated the extraction of cadmium from aqueous solutions. Several chemical variables were optimized in order to obtain high extraction outputs. Parameters such as concentration of the ligand, pH, and amount of buffer solution were optimized to enhance the formation of cadmium complex. The SFODME method was assisted by dispersion of extractor solvent into aqueous solutions using 2-propanol. Under the optimum extraction and instrumental conditions, the limit of detection and limit of quantitation values obtained for cadmium using the combined methods (SFODME-SQT-FAAS) were found to be 0.4 and 1.3 mu g L-1, respectively. Matrix effects on the method were also examined for tap water and wastewater, and spiked recovery results were found to be very satisfactory.
Keywords: Cadmium; Solidified floating organic drop microextraction; Slotted quartz tube; Flame atomic absorption spectrometry; WATER SAMPLES; LEAD; REMOVAL; CU; Environmental Sciences & Ecology